Mrs. Noodlekugel and Drooly the bear - Pinkwater, Daniel Manus, 1941- (Pinkwater, Daniel Manus, 1941- Mrs. Noodlekugel, 2015)
"In a wonderfully loopy third episode, Nick and Maxine are surprised to meet Captain Noodlekugel, back from the sea with a somewhat untrainable bear."--Amazon.com.